Urgent advice on lumpy skin disease - EFSA Panel on Animal Health and Welfare (EFSA Journal, 2016)
Abstract In order to assess the effects on disease spread and persistence of partial stamping out of only clinically affected animals in holdings where the presence of lumpy skin disease has been confirmed, against total stamping‐out policy of infected herds coupled with vaccination, a mathematical model for the transmission of LSDV between farms was developed and different scenarios explored. According to the model, vaccination has a greater impact in reducing LSDV spread than any culling policy, even when low vaccination effectiveness is considered. When vaccination is evenly applied so that 95% of the farms are vaccinated with 75% of vaccinated animals effectively protected, then total stamping out and partial stamping out result in a similar probability of eradicating the infection. When no vaccination is applied or when vaccination has a lower effectiveness (e.g. 40%), the probability of eradication is higher when total stamping out is performed as compared to partial stamping out. In general, partial stamping out results in limited increase of the number of farms affected as compared to total stamping out. Independently of the culling interventions applied in the model, vaccination was most effective in reducing LSDV spread if protection had already been developed at the time of virus entry, followed by protection of herds after virus entry. No vaccination is the least effective option in reducing LSDV spread. In order to reach the above described effects, it is necessary to implement vaccination of the entire susceptible population in regions at risk for LSDV introduction or affected by LSDV in order to minimise the number of outbreaks, and high animal‐ and farm‐level vaccination coverage should be achieved. Farmers and veterinarians should be trained in the clinical identification of LSD in order to reduce underreporting, and the effectiveness of partial stamping out should be evaluated under field conditions.